2014
DOI: 10.1080/00221686.2014.932855
|View full text |Cite|
|
Sign up to set email alerts
|

On the Reynolds number sensitivity of smoothed particle hydrodynamics

Abstract: This work investigates the Reynolds number sensitivity of the weakly compressible smoothed particle hydrodynamics method. A mode of instability previously reported for Poiseuille flow is systematically analysed for six relevant test cases. We discuss the influence of the presence of physical viscosity, investigate the origin of the instability for the Couette flow example and explore its implications on convergence properties. Moreover, a novel instability of slightly different nature, which arises in pipe flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Through the assumption of suitable inflow and outflow buffer particles, this algorithm allows the enforcement of different inlet/outlet boundary conditions. This inflow/outflow algorithm has also been successfully applied to model a broad range of flow processes such as the interaction between freesurface steady currents and boats or bluff bodies (Marrone et al, 2013), gated spillway flows (Saunders et al, 2014), flow separation at bends (Hou et al, 2014) and flow over sills and weirs (Meister et al, 2014). In this context, the modeling of jets discharged into reservoirs and channel flow through the SPH technique needs appropriate inlet/outlet boundary conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Through the assumption of suitable inflow and outflow buffer particles, this algorithm allows the enforcement of different inlet/outlet boundary conditions. This inflow/outflow algorithm has also been successfully applied to model a broad range of flow processes such as the interaction between freesurface steady currents and boats or bluff bodies (Marrone et al, 2013), gated spillway flows (Saunders et al, 2014), flow separation at bends (Hou et al, 2014) and flow over sills and weirs (Meister et al, 2014). In this context, the modeling of jets discharged into reservoirs and channel flow through the SPH technique needs appropriate inlet/outlet boundary conditions.…”
Section: Introductionmentioning
confidence: 98%
“…In the literature, Federico, Marrone, Colagrossi, Aristodemo, and Antuono (2012) and Shakibaeinia and Jin (2010) used SPH to study a uniform laminar open channel flow of low Reynolds Number and validated their model by initializing and updating the analytical velocity and pressure profiles on the inflow boundary. Later Meister, Burger, and Rauch (2014) used the same numerical technique for steady laminar open channel flows with different water viscosities. Their results demonstrated that for highly viscous flow, the streamwise velocities agreed well with analytical solutions; however, when the viscosity was reduced close to the actual value of water, the predicted velocities gradually deviated from the analytical predictions.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the implementation of this artificial viscosity could lead to unphysically high shear viscous forces because SPH simulations are stabilized by the physical viscosity of a fluid, and it is challenging to simulate low viscous flows [34]. Therefore, our simulations will be carried out with this high viscous setting.…”
Section: The Sph Equationsmentioning
confidence: 99%